Selected Papers from 27th European Biomass Conference & Exhibition (EUBCE 2019) - Baxter, David; Mussatto, Solange I. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book draws together a small selection of full-length papers based on presentations given at the 27th European Biomass Conference and Exhibition held in Lisbon, Portugal in 2019. The topics covered, which reflect the breadth of the program of the EUBCE conference itself, include biomass sources, various aspects of technologies used for the conversion of biomass to bioproducts and bioenergy, as well as different approaches to assessing environmental impacts, which include case studies based on different technologies in use in a range of countries.